A study on commercial property pricing in Uganda - Mirembe, Rachael Daisy (Department of Construction Economics and Management, 2023)
Property developers and investors seek to understand the drivers of prices for office and retail space. Through literature, we learn that size and age, locational attributes, physical features of the properties, and economic variables are significant determinants of commercial property prices. However, previous work has narrowly focused on aspects akin to formal structures and ignored the role of institutions, especially conventions and social norms incredibly, and what influences the behaviour of the property developers and investors while making the pricing decision. Therefore, the goal of this study was to understand how prices for commercial properties are determined in Uganda. The objectives of the study were to understand the role of conventions and social norms found in the property market environment on price determination and to explore the behaviour tendencies/heuristics exhibited by the players during the pricing decision-making process. The study was qualitative in nature. The researcher interviewed property owners, developers, institutional investors, and key informants to understand the conventions and social norms that exist in the property market and how they ultimately influence the pricing decision of commercial buildings. This study reveals that conventions exist in the Ugandan property markets. The conventions signal a price to the players in the property environment. However, due to information asymmetry and irrationality, each player interprets the price signals differently, using heuristics to develop the final price. This study helps researchers understand the role of individual behaviour/heuristics in advancing our understanding of institutions and the effects of the two on commercial property pricing, the economy at large and its consequences on economic policy.